Experimental research on desorption characteristics of gas-bearing coal subjected to mechanical vibration. Issue 5 (September 2020) - Chen, Xuexi; Zhang, Liang; Shen, Maoliang
Mechanical vibration can induce coal and gas outburst accidents, and can also promote the exploitation of coalbed methane. In this paper, a vibration-adsorption-desorption experiment system was established, the effects of coal sample particle diameter, gas pressure, and vibration frequency on gas desorption were studied. Mechanical vibration can generate a shear force in the adsorbed gas and promote gas desorption, but there are appropriate vibration parameters. Within the range of experimental parameters, the larger the amplitude, the more favorable for gas desorption. The change rules of gas desorption rate and desorption quantity under different conditions are basically the same, showing a power function shape with time increase, and most of the desorption quantity was completed within the first 5 minutes. The gas desorption rate and desorption quantity were positively related to the gas adsorption pressure. The results have great reference value for preventing gas outbursts and promoting gas exploitation.